The Functional Response of Mesenchymal Stem Cells to Electron‐Beam Patterned Elastomeric Surfaces Presenting Micrometer to Nanoscale Heterogeneous Rigidity. Issue 39 (1st September 2017) - Biggs, Manus J. P.; Fernandez, Marc; Thomas, Dilip; Cooper, Ryan; Palma, Matteo; Liao, Jinyu; Fazio, Teresa; Dahlberg, Carl; Wheadon, Helen; Pallipurath, Anuradha; Pandit, Abhay; Kysar, Jeffrey; et al.
Abstract: Cells directly probe and respond to the physicomechanical properties of their extracellular environment, a dynamic process which has been shown to play a key role in regulating both cellular adhesive processes and differential cellular function. Recent studies indicate that stem cells show lineage‐specific differentiation when cultured on substrates approximating the stiffness profiles of specific tissues. Although tissues are associated with a range of Young's modulus values for bulk rigidity, at the subcellular level, tissues are comprised of heterogeneous distributions of rigidity. Lithographic processes have been widely explored in cell biology for the generation of analytical substrates to probe cellular physicomechanical responses. In this work, it is shown for the first time that that direct‐write e‐beam exposure can significantly alter the rigidity of elastomeric poly(dimethylsiloxane) substrates and a new class of 2D elastomeric substrates with controlled patterned rigidity ranging from the micrometer to the nanoscale is described. The mechanoresponse of human mesenchymal stem cells to e‐beam patterned substrates was subsequently probed in vitro and significant modulation of focal adhesion formation and osteochondral lineage commitment was observed as a function of both feature diameter and rigidity, establishing the groundwork for a new generation of biomimetic material interfaces. Abstract : Cellular rigidity‐sensing mechanisms in response to discrete areas of modulated rigidity are not understood. A new class of biomimetic surfaces comprising micro‐ to nanopatterned rigidity by focused electron beam exposure is described. Heterogeneous rigidity substrates induce significant changes to focal adhesion colocalization and osteochondral function in mesenchymal stem cell populations as a function of spot size and spot rigidity.